2021
DOI: 10.1101/2021.06.24.21259453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conditionality of COVID-19 vaccine acceptance in European countries

Abstract: The COVID-19 vaccine rollout in recent months offers a powerful preventive measure that may help control SARS-CoV-2 transmission. Nevertheless, long-standing public hesitation around vaccines has heightened public health concerns that vaccine coverage may not achieve desired public health impacts.This cross-sectional survey was conducted online in December 2020 among 7000 respondents (aged 18 to 65) in Belgium, France, Germany, Italy, Spain, Sweden, and Ukraine. The survey included open text boxes for fuller e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Within our study, women expressed higher levels of refusal or reluctance towards COVID-19 vaccination (OR = 2.31, CI: 1.38-3.89). This is in line with ndings described by Heyerdahl et al (43), who observed that French women exhibited the highest COVID-19 vaccine hesitancy when compared to their European counterparts. Vaccine safety and mistrust of the authorities were again the most commonly reported motives of hesitancy.…”
Section: Comparison With Body Of Evidencesupporting
confidence: 93%
“…Within our study, women expressed higher levels of refusal or reluctance towards COVID-19 vaccination (OR = 2.31, CI: 1.38-3.89). This is in line with ndings described by Heyerdahl et al (43), who observed that French women exhibited the highest COVID-19 vaccine hesitancy when compared to their European counterparts. Vaccine safety and mistrust of the authorities were again the most commonly reported motives of hesitancy.…”
Section: Comparison With Body Of Evidencesupporting
confidence: 93%
“…This is important to understand because it means that we cannot take their current vaccine acceptance for granted, it is based on current social and political conditions and patterns which can change. 42 This aligns with the study of expected vaccine uptake, 43 which found that both conditional acceptance and rejection of COVID-19 vaccines were dynamic and volatile. Through following up with the same participants, we were able to see that people’s location along the hesitancy/acceptance spectrum is changeable.…”
Section: Discussionsupporting
confidence: 71%
“…COVID‐19 vaccination rates also seem to be comparatively low in Ukraine 49 . By late February 2022, the Our World in Data website reported that only 36.3% of the Ukrainian population was completely vaccinated, having received two doses against COVID‐19 122…”
Section: Resultsmentioning
confidence: 99%
“…After duplicates were removed, the titles and abstracts of 1,628 reports were reviewed by one of the authors (JFL), and 131 met the eligibility criteria (Figure 1). The current review was primarily based on 107 full papers, 2‐108 but, due to the scarcity of data, we also chose to cite five relevant abstracts 109‐113 for a more complete picture of child health in Ukraine. Our literature search was limited to papers published in English.…”
Section: Methodsmentioning
confidence: 99%